2021
DOI: 10.1111/rda.14004
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oestrus by administering Inhibin antiserum along with equine chorionic gonadotropin in anoestrous bitches

Abstract: As dogs experience oestrus only once or twice a year, it is necessary to establish an effective method of oestrous induction for efficient breeding. In the present study, we evaluated inhibin antiserum (IAS) on oestrous induction in anoestrous females. Bitches were administered 0.5 ml/kg IAS or a mixture of 50 IU/kg equine chorionic gonadotropin (eCG) and 0.5 ml/kg IAS and 500 IU human chorionic gonadotropin (hCG) administered 7 days after the mixture injection. As a control, bitches received 50 IU/kg eCG, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Moreover, 80% of these animals became pregnant after natural mating or artificial insemination [ 119 ]. Recently, it was reported that inhibin anti-serum, in combination with eCG, induced estrus and promoted a considerable number of ovulations in anestrus dogs [ 120 ]. These findings and further studies may contribute to the development of canine ARTs.…”
Section: Postscriptmentioning
confidence: 99%
“…Moreover, 80% of these animals became pregnant after natural mating or artificial insemination [ 119 ]. Recently, it was reported that inhibin anti-serum, in combination with eCG, induced estrus and promoted a considerable number of ovulations in anestrus dogs [ 120 ]. These findings and further studies may contribute to the development of canine ARTs.…”
Section: Postscriptmentioning
confidence: 99%